Myriad Manifestations of Gallbladder Carcinoma on Multidetector Computed Tomography: Retrospective Study of 230 Patients from Tertiary Care Centre of North India - Gupta, Varun; Lohia, Nishant; Harish S; Sawant, Milind; Bharadwaj , Yogesh Kumar (Asian Journal of Medical Sciences, 2022)
Background: Gallbladder carcinoma is endemic in India. Though imaging findings of gallbladder carcinoma are very well-described in the literature, the research question that guided this study was to evaluate various imaging manifestations of the disease in this particular geographic region of North India which is a highly endemic region for gallbladder cancer and compare with studies from other parts of the world. Aims and Objective: The purpose of the study was to retrospectively analyse spectrum of findings on Multidetector Computed Tomography (MDCT) in histologically proven gallbladder carcinoma detected at a tertiary care centre from the NorthIndia. The primary objective was to define the various patterns of growth while the secondary objective was to analyse the specific prevalence and patterns of spread of the disease. Materials and Methods: We retrospectively studied contrast enhanced Computed Tomography (CECT) findings in 230 patients of histologically proven gallbladder carcinoma. Patients with previous cholecystectomy or biliary intervention were excluded. Results: In our study, focal or asymmetrical wall thickening of the gallbladder was the most common growth pattern seen in 140(61%) patients. Contiguous infiltration of liver was seen in 190 (83%) cases. Regional nodal involvement was observed in 90 (39%) patients, while 100 (43%) patients had both regional & distant nodal involvement. Liver and peritoneal metastases were noted in 71 (31%) patients and 96 (42%) patients respectively. Majority (81%) of patients had stage IV disease. Conclusion: MDCT provides comprehensive information regarding the local extent as well as distant spread of gallbladder carcinoma. Asymmetric gall bladder wall thickening in this geographical region must be considered suspicious and should evoke histopathological analysis to exclude malignancy.